Comparison of immunophenotypes between Rag2 knockout mice derived from two different sources - Yu Jeong Roh; Jeong Eun Gong; Ji Eun Kim; You Jeong Jin; Hee Jin Song; Ayun Seol; Jumin Park; Yong Lim; Dae Youn Hwang (Laboratory Animal Research, 2023)
Abstract Background Recombination activating gene2 (Rag2) knockout (KO) mice are used widely in various research fields, including vaccine development, transplantation studies, and hematopoiesis research, but few studies have compared their phenotypes. This study examined whether there were differences in the immunophenotypes between Rag2 KO mice derived from different sources. In particular, the changes in the organ weight, histological structure, and subpopulation of T and B cells were compared in the spleen and thymus of C57BL/6-Rag2em1hwl/Korl (Rag2/Korl KO) and B6.Cg-Rag2tm1.1Cgn/J (Rag2/J KO) mice. Results The weight of the spleen and thymus similarly decreased in the Rag2/Korl and Rag2/J KO mice compared to their wild type (WT) mice, even though the other organs were kept at the same weight. A slight difference between the Rag2/Korl and Rag2/J KO group were detected in the number of white blood cells (WBC), lymphocytes (LYM), red cell distribution width (RDW), and platelets (PLT). In addition, the white pulp of the spleen and the cortex region of the thymus decreased in both Rag2 KO mice compared to WT mice. On the other hand, significant differences in the number of CD8+ T and B cell subpopulations between WT and Rag2 KO mice were observed between Rag2/Korl and Rag2/J KO group, while the CD4+ T subpopulation was maintained similarly in both groups. Conclusions These results suggest that Rag2/Korl and Rag2/J KO mice exhibit similar immunophenotypes in the spleen and thymus except for the differences in the number of CD8+ T and B cell subpopulations.